Evaluation of Ovulation Inhibition Properties of a Phytoestrogen Isolated from Momordica charantia Linn. Seeds - Patil, Sharanabasappa A. (Journal of Pharmacy and Nutrition Sciences, 2013)
Background and objectives: Momordica charantia Linn. has been used as a dietary / medicinal supplement for health care. The plant has a long history in worldwide people for the usage of vaginal discharge, to promote menstruation and to induce abortions. However, the mechanism of action for its ovulation inhibition effects is not clearly known. Therefore, the present study was carried out to evaluate the ovulation inhibition properties of phytoestrogenic molecule isolated from M. charantia seeds in albino rats as an experimental model. Methods: Ovulation inhibition properties of fractions of ethanol extract and phenolphthalein a phytoestrogenic molecule isolated from seeds of Momordica charantia Linn. were evaluated in fertile female albino rats. In the first batch of animals having groups I, II, III, IV were treated with 15 and 25mg/100g oral doses of Fraction I and Fraction II and group V served as control. In the second batch of animals having groups I, II, III was treated with 10, 15 & 20mg/100g isolated phenolphthalein and group IV served as control. Results: At autopsy on day 31st, decrease in ovarian weight and histological studies shows highly significant decrease in number of developing follicles, Graafian follicles, corpora lutea and significant increased in number of atreatic follicles is observed in Fraction I and phenolphthalein treatment. There are no appreciable changes are observed in the above parameters when both the doses of Fraction II administration. Interpretation and Conclusions: The study results suggested that M. charantia seed fractions and phenolphthalein possess ovulation inhibition properties in experimental animals. Interestingly, in recent years, the popularity of different kinds of pharmaceutical preparations containing phytoestrogens has constantly increasing. Therefore, studies of the influence of the above mentioned plant components on female reproduction have become more and more important. This leads to discovery of newer phytoconstituents with better activities and provide source of new biomolecules for biologists to work on. The studies explore the utilization of medicinal plants for effective management of contraception. It gives a larger platform for the medicinal plant growers by providing scientific support and data to the traditional invalidated herbal drugs. Taking account of all these facts, the present study was undertaken in albino rats.